Early diagnostic indicators of return to training and competitive activity in ice-hockey players after traumatic brain injuries - Sekretnyi , Volodymyr; Nekhanevych , Oleg (The Ukrainian Scientific Medical Youth Journal, 2022)
The aim of study is to develop the criteria for early recovery after sport-related concussions (SRC) with ice-hockey players. 30 professional ice-hockey players from 17 to 30 years (average age 22.7 ± 0.8 from SMS) were included in study. Methods: somatoscopy and somatometry, assessment of autonomic nervous system (ANS), assessment of heart rate variability (HRV), assessment of balance (BESS test). The Buffalo concussion treadmill test (BCTT), which is the most used physicalactivity test after SRC was performed on days 3 and 4 after SRC. The results of the study showed a link between SRC and changes in autonomic regulation in the case of increased sympathicotonia. In addition, we discover the dynamics of ANS stability during the early period of recovery after SRC. Also, we establish improvement of motor functions after SRC in the dynamics from 1 visit to 4. However, despite the existing recommendations for early active rehabilitation on the third day after concussion, not taking into account the level of autonomic regulation can lead to physical overstrain of regulatory systems. This think shows the importance of taking into account the level of autonomic regulation while planning the rehabilitation and sports activities after SRC with ice-hockey players.